PAMALI PADA PEREMPUAN HAMIL DI MASYARAKAT BANJAR KALIMANTAN SELATAN (KAJIAN ANTROPOLOGI SASTRA) - Syarah Veniaty (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
Pamali to pregnant women in the Banjar community of South Kalimantan is a type of oral tradition whose existence still exists today. Pamali is a prohibition/taboo that regulates the behavior, speech, and lifestyle of a pregnant woman in society. The sentence 'pamali' has an accompanying 'effect' if the offender breaks it. Based on this, pamali in pregnant women is studied from the perspective of literary anthropology. This type of research is qualitative-description which aims to describe the forms and aspects of literary anthropology in this Pamali. From the results of the research, it was found that 15 pamali were grouped into 4 forms based on aspects of habit, manners, unseen things and types of food. Most of these pamali are analogies of certain objects with the body parts of a pregnant woman and the baby she is carrying. So, many Banjar people still believe in this pamali-pamali to avoid bad things during pregnancy.